2006
DOI: 10.1186/1471-2350-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase gene polymorphisms and haplotype analysis in a stroke population

Abstract: Background: Paraoxonase (PON) has anti-atherogenic activity due to its protective function against low density lipoprotein (LDL) oxidation. Alteration of enzyme activity due to polymorphisms in the PON genes may influence the development of atheroma and thus affect stroke risk. Three PON genes (PON1, PON2 and PON3) have been identifiedand mapped to chromosome 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
2
46
0
1
Order By: Relevance
“…The G/G genotype frequency in Adjaethnic group (10.0 %) was similar to that observed in Chinese Li minority (8.0 %), but was significant different from that observed inAdjaethnic group (19.0 %).There were also significant differences in PON3 Ala99Ala polymorphism distribution in Beninese AdjaandMahiethnic groups compared to British Caucasians (p<0.05) (Robertson, 2003;Pasdar, 2006). Additional studies on large cohorts from different ethnic groups in Benin may be needed to determine the real genotypes distribution of PON3 Ala99Ala polymorphism in Beninese population…”
Section: Discussion:-supporting
confidence: 54%
See 1 more Smart Citation
“…The G/G genotype frequency in Adjaethnic group (10.0 %) was similar to that observed in Chinese Li minority (8.0 %), but was significant different from that observed inAdjaethnic group (19.0 %).There were also significant differences in PON3 Ala99Ala polymorphism distribution in Beninese AdjaandMahiethnic groups compared to British Caucasians (p<0.05) (Robertson, 2003;Pasdar, 2006). Additional studies on large cohorts from different ethnic groups in Benin may be needed to determine the real genotypes distribution of PON3 Ala99Ala polymorphism in Beninese population…”
Section: Discussion:-supporting
confidence: 54%
“…The expression of PON3 gene occurs mainly in the liver and bind to HDL in blood stream (Reddy et al, 2001). The PON3 gene has five commons Single Nucleotide Polymorphisms (SNPs) Ala99Ala, Asp107Asn, Glu146Lys, Ala179Asp and Tyr233Cys (Robertson et al, 2003;Li et al, 2004;Pasdar et al, 2006 andSanghera et al, 2008). Despite the importance of the paraoxonase gene and its implications on the genetic susceptibility to coronary heart disease, no studies on African black populations have been reported.…”
mentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Liu et al in 2013 conducted and published a systematic review and meta-analysis of 28 selected studies addressing these relationships. 21 They found that the R allele and the RR genotype of PON1 Q192R polymorphism correlated with a higher risk for ischemic stroke in the general population.…”
Section: Pon1 and Ischemic Strokementioning
confidence: 99%
“…PON promoter and coding region polymorphisms were shown to be associated with increased stroke and coronary artery disease risk in several studies, 175,[182][183][184] but a recent study of the polymorphisms in PON I, PON II, and PON III in ischemic stroke patients showed no association with an increased risk of ischemic stroke. 185 …”
Section: Paraoxonase (Pon)mentioning
confidence: 99%